Olfactory dysfunction: A plausible source of COVID-19-induced neuropsychiatric symptoms - Tai, Alan Pui-Lun; Leung, Mei-Kei; Lau, Benson Wui-Man; Ngai, Shirley Pui-Ching; Lau, Way Kwok-Wai (Frontiers in Neuroscience, 2023)
Olfactory dysfunction and neuropsychiatric symptoms are commonly reported by patients of coronavirus disease 2019 (COVID-19), a respiratory infection caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Evidence from recent research suggests linkages between altered or loss of smell and neuropsychiatric symptoms after infection with the coronavirus. Systemic inflammation and ischemic injury are believed to be the major cause of COVID-19-related CNS manifestation. Yet, some evidence suggest a neurotropic property of SARS-CoV-2. This mini-review article summarizes the neural correlates of olfaction and discusses the potential of trans-neuronal transmission of SARS-CoV-2 or its particles within the olfactory connections in the brain. The impact of the dysfunction in the olfactory network on the neuropsychiatric symptoms associated with COVID-19 will also be discussed.